2013
DOI: 10.1016/j.jaci.2013.01.022
|View full text |Cite
|
Sign up to set email alerts
|

IgE cross-reactivity between the major peanut allergen Ara h 2 and the nonhomologous allergens Ara h 1 and Ara h 3

Abstract: Occurrence of similar sequences in the 3 major peanut allergens accounts for the high extent of cross-reactivity among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 43 publications
8
82
0
4
Order By: Relevance
“…All but 1 of the patients who were sensitized to Ara h 2 and Ara h 6 showed concomitant sensitization to Ara h 1 and/or Ara h 3. Our findings are in line with others showing that Ara h 2 is the most important peanut allergen [1,2,3,4,5,6,11,21,22]. Data about the prevalence and diagnostic value of Ara h 6 are rare, but in accordance with our results two studies showed that both peanut 2S albumins are recognized by IgE from the same patients in almost all cases and that the diagnostic accuracy of IgE specific to Ara h 6 in adults is as good as for Ara h 2 [1,7].…”
Section: Discussionsupporting
confidence: 93%
“…All but 1 of the patients who were sensitized to Ara h 2 and Ara h 6 showed concomitant sensitization to Ara h 1 and/or Ara h 3. Our findings are in line with others showing that Ara h 2 is the most important peanut allergen [1,2,3,4,5,6,11,21,22]. Data about the prevalence and diagnostic value of Ara h 6 are rare, but in accordance with our results two studies showed that both peanut 2S albumins are recognized by IgE from the same patients in almost all cases and that the diagnostic accuracy of IgE specific to Ara h 6 in adults is as good as for Ara h 2 [1,7].…”
Section: Discussionsupporting
confidence: 93%
“…The eight epitopes identified for Ara h 2, that are similar to those previously reported, include the epitopes that have been recently shown to be responsible for cross-reactivity with Ara h 1 and Ara h 3 [38, 46, 49]. Seven epitopes were newly identified for Ara h 6 (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…We were able to establish 2 ELISA systems for the reliable determination of Ara h 2 and Ara h 6 in the complex breast milk matrix without any relevant cross-reactivity against single allergens and extracts which have been selected for structural similarities, sequence identities, and a phylogenetic relationship. The included allergens and allergen sources for cross-reactivity studies were chosen according to their structure similarities with Ara h 2 and Ara h 6, which are the cross-reactive counterparts Ara h 6 and Ara h 2, respectively, the α-amylase-inhibitor [27], and the peanut allergen Ara h 1, which was described as being IgE cross-reactive because of high sequence similarity on surface-exposed loops [28]. However, none of the investigated allergens were detected by the newly developed Ara h 2 and Ara h 6 sandwich ELISAs.…”
Section: Discussionmentioning
confidence: 99%